2022
DOI: 10.3390/cancers14071835
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Neoplasms of the Gynecologic Tract

Abstract: Gynecological tract neuroendocrine neoplasms (NEN) are rare, aggressive tumors from endocrine cells derived from the neuroectoderm, neural crest, and endoderm. The primary gynecologic NENs constitute 2% of gynecologic malignancies, and the cervix is the most common site of NEN in the gynecologic tract. The updated WHO classification of gynecologic NEN is based on the Ki-67 index, mitotic index, and tumor characteristics such as necrosis, and brings more uniformity in the terminology of NENs like other disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 110 publications
(203 reference statements)
1
24
0
Order By: Relevance
“…All NECs included in this study showed significantly higher overall metastatic rates than non-NECs of the same primary sites. These findings are consistent with previous reports on NECs in the female genital tract [ 2 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…All NECs included in this study showed significantly higher overall metastatic rates than non-NECs of the same primary sites. These findings are consistent with previous reports on NECs in the female genital tract [ 2 , 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, the regimen given is similar to NEC alone. Although there are no optimal treatment guidelines for this subgroup, surgery is recommended and followed by adjuvant therapy in the early stage [ 4 ]. Our patient, with an initial diagnosis of FIGO IB2, underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them present a pure form, and only 4% of this type of tumor is associated with adenocarcinoma [ 2 , 3 ], much less common with squamous cell carcinoma. Overall, NENs of the gynecologic tract are uncommon and aggressive, with high recurrence rates and dismal prognosis, making their treatment challenging [ 4 ]. In a study by Crane et al [ 5 ], the origin of these neoplasms in the cervix is highest, at 54%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It commonly arises in the lung and only 2.5%–5% are extrapulmonary 1–3. Primary SCNC of the female genital tract constitutes less than 2% of all gynaecological cancers 4–6. It has been reported in the cervix, endometrium, ovary, vagina and vulva.…”
Section: Introductionmentioning
confidence: 99%